Multiple Pregnancy New Insights - Abduljabbar, Hassan S. (IntechOpen, 2023)
This book discusses an important topic in obstetrics, that of multiple pregnancies. Multiple pregnancy may be determined via clinical history, physical pelvic examination, blood test, or pelvic ultrasound. Babies may be delivered vaginally or via Cesarean section and there is the possibility of complications due to early delivery, which may lead to long- or short-term health problems for the infant. This book addresses these issues in four sections that discuss the basic aspects of multiple pregnancies, diagnosis of multiple pregnancy, breastfeeding, and complications related to multiple pregnancies.